Analysis on the mechanical response of composite pressure vessels during internal pressure loading: FE modeling and experimental correlation. (1st May 2021) - Nebe, M.; Soriano, A.; Braun, C.; Middendorf, P.; Walther, F.
Abstract: Commercial development of gaseous hydrogen storage in fuel cell electric vehicles is inevitably subjected to reliable and cost-effective design of composite pressure vessels. In this context, certainty in the design process is sought, which is determined by how well the vessel's mechanical response is understood, but more importantly to which accuracy the final collapse can be predicted. As such, a symbiosis of numerical and experimental work appears as a leading path towards robust design methodologies, where both analyses complement and scrutinize each others validity. This research presents the analysis on the mechanical response of composite pressure vessels during internal pressure loading through the correlation of numerical and experimental results on various degrees of complexity. Based on an extensive experimental dataset, a three-dimensional FE model is implemented on a realistic vessel geometry, evaluating its constitutively elastic behavior, and its response under failure and damage progression. Likewise, an established experimental framework is used to derive data by means of contour scans, outer surface strains, airborne acoustic emissions and final burst pressure. The precise recreation of the vessel geometry, together with the detailed analysis approach, permits to show a reasonable agreement between the predicted and the measured structural responses, the sequence of damage onset, and the final collapse occurring in the cylindrical region ( < 1%). Discrepancies still exist because of the remaining uncertainty concerning the individual layer geometry and the characterization of damage in the helical plies. Altogether, through the alignment of experimental and numerical analyses, this work provides the base for further optimization frameworks, in which an adequate representation of the vessel's meridional thickness profile and material properties stands out as necessary feat to accurately reproduce the mechanical response and final strength in a time- and cost-effective design process.